Video Playback Speed Influence on Learning Effect From the Perspective of Personalized Adaptive Learning: A Study Based on Cognitive Load Theory - Mo, Chuan-Yu; Wang, Chengliang; Dai, Jian; Jin, Peiqi (Frontiers in Psychology, 2022)
Following the Covid-19 pandemic, online learning has become a new mode of learning that students must adapt to. However, the mechanisms by which students receive and grasp knowledge in the online learning mode remain unknown. Cognitive load theory (CLT) offers instructions to students considering the knowledge of human cognition. Therefore, this study considers the CLT to explore the internal mechanism of learning under the online mode in an experimental study. Recruiting 76 undergraduates and randomly assigning them to four speed types (1.0x, 1.25x, 1.5x, and 2x), the study observed and analyzed how video playback speed affected students’ learning and cognitive load, to obtain the following results: (1) Video playback speed significantly influenced the students’ learning effect. The best effect was observed at the speed of 1.25x and 1.5x. (2) The speed that affected learning effect best differed according to the students’ learning abilities. High-level group students performed best at the speed of 1.5x, whereas low-level group students performed best at the speed of 1.25x. (3) The 1.5x speed showed significant differences in learning effect by students’ majors. This indicates that the cognitive load of liberal arts students increased greatly at this speed. (4) Change in playback speed has a significant impact on cognitive load. Accelerated playback speed increases the cognitive load of students. The highest learning effect is observed under medium cognitive load.